Infant-feeding Practices among HIV-infected Mothers in an HIV-treatment Programme - Sadoh, Wilson E; Sadoh, Ayebo E; Adeniran, Kayode A; Abhulimhen-Iyoha, Blessing I (Journal of Health, Population and Nutrition, 2009)
The transmission of HIV via breastmilk has led to various recommendations for HIV-infected mothers. In this study, the feeding practices of HIV-infected mothers in the first six months of their infants' lives were evaluated. In total, 103 consecutive mothers of children, aged 6-24 months, were evaluated for their feeding practices in the first six months of their infants' lives. The mothers were recruited in two cohorts based on their entry (PMTCT cohort) or non-entry (non-PMTCT cohort) to an HIV MTCT-prevention programme. Information obtained included maternal age, socioeconomic class, and the educational level attained. All the babies in the non-PMTCT cohort were breastfed compared to none in the PMTCT cohort. Infant formula was inadequately prepared for 77.42% of babies in the non-PMTCT cohort compared to 18.64% in the PMTCT cohort. The mixed-feeding rate was high (70.45 %) in the non-PMTCT cohort. Over 70% of babies in both the cohorts were bottle-fed. Voluntary counselling and testing services in the healthÂcare system should be strengthened. All mothers should receive infant-feeding counselling, with exclusive breastfeeding being encouraged in those with unknown HIV status. Key words: Antiretroviral therapy; Breastfeeding; Counselling; HIV; Infant-feeding practices; Infant food; PMTCT; Nigeria doi:10.3329/jhpn.v26i4.1890 J Health Popul Nutr 2008 Dec:26(4):463-467